P204 Secondary organizing pneumonia caused by Aspergillus flavus in immunocompromised patients. (20th September 2022) - Gupta, Chhavi; Yadav, Sapna; Sircar, Mrinal; Gupta, Rajesh; Chavhan, Neela; Mehra, Saurabh; Koolwal, Prateek; Kumar, Sunny; Singh, Sujeet; Deshpande, Anurag; Anand, Siddharth; Kaur, Ravneet
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Introduction: Fungal pneumonia is a known complication in immunocompromised patients. However fungal infection leading to organizing pneumonia (OP) is a rare entity. Here we present two cases of co-occurrence of OP with Aspergillus lung infection Case 1: A 33-year-old male with a history of recurrent oral-genital ulcerations and low-grade fever for the last 3 months presented with shortness of breath and high-grade fever for 10 days. On presentation he was hypotensive, tachycardic, and tachypneic, examination revealed bilateral crackles. His initial investigations were hemoglobin (Hb) 8.8, total leucocyte counts (TLC) 13 000, platelet 190 000, liver function test (LFT), and kidney function test (KFT) were normal. High-resolution commuted tomography (HRCT) revealed multifocal areas of interlobular septal thickening with ground glass opacity and patchy areas of consolidation seen in bilateral lung fields (Fig. 1). He was initially managed with broad-spectrum antibiotics and oxygen support by a high flow nasal cannula (HFNC); as the condition deteriorated, he was mechanically ventilated. Fibreoptic bronchoscopy with bronchoalveolar lavage (BAL) was performed. Investigations for tuberculosis, nocardia, pneumocystis carinii, and bacterial infection in BAL was negative. Galactomannan index (GMI) in BAL was 3.15 and grew Aspergillus flavus . Transbronchial biopsy revealed features consistent with organizing pneumonia. He was started on voriconazole and steroids. He was diagnosed with undifferentiated connective tissue disorder. As the patient's condition improved in due course of time, he was extubated and discharged in stable condition on voriconazole and steroids and is currently doing fine. Case 2: A 56-year-old male known case of mantle cell lymphoma on consolidation therapy, presented with 15 days history of shortness of breath and high-grade fever. Chest examination revealed decreased breath sounds bilaterally in the lower lung zones with lower zone crackles. Initial investigations showed Hb 10.9, TLC 3.90, platelet 150000, KFT and LFT were normal. HRCT scan revealed multilobular areas of consolidation showing air bronchogram with ground glass opacities in bilateral lung (Fig. 1). Bronchoalveolar lavage fluid (BALF) revealed the growth of Aspergillus flavus and was GMI 1.97. Investigations for tuberculosis, nocardia, pneumocystis carinii and bacterial infection was negative. Transbronchial biopsy revealed features consistent with organizing pneumonia. He was started on combination therapy with voriconazole and micafungin along with steroids. Initially, he was managed with oxygen support but his oxygenation gradually worsened, he was mechanically ventilated, and received multiple pruning sessions. Patient had refractory organizing pneumonia, did not show any improvement even after 1 month, and left against medical advice. Conclusion: Bacterial and viral infections are the common causes of secondary OP. Fungal infections implicated in secondary OP are rarely described, of which there are reports of Pneumocystis jiroveci (PJP) and Penicillium infection leading to secondary OP. Aspergillus flavus is a ubiquitous fungal agent and is considered as pathogenic in immunocompromised settings can lead to secondary organizing pneumonia. High index of suspicious for OP is always to be kept in mind while treating Aspergillus flavus pneumonia.